(untitled) (International Journal on Stereo & Immersive Media, 2025)
The Lippmann process is a unique method for capturing and reproducing colour, and it stands as one of the first colour photographic processes ever invented (1891). This extraordinary achievement earned its inventor, Gabriel Lippmann, the Nobel Prize in Physics in 1908. It records the standing waves formed when light reflects off a surface, such as the interface between air and the photosensitive emulsion. These standing waves are “imprinted” within the emulsion, which contains crystals small enough to capture the details of these waves, ranging from 170 nm to 350 nm.